Correlation of Anti-HLA IgA Alloantibodies and Fc Receptor Motives with Kidney Allograft Survival - Arnold, Martin; Steffen, Ulrike; Wiesener, Michael; Bach, Christian; Spriewald, Bernd; Lindemann, Monika (Immuno, 2022)
Immunoglobulin A (IgA) is the most abundant antibody isotype in humans and anti-HLA IgA was found in sera of transplant recipients. Focusing on patients awaiting kidney re-transplantation, we tested the impact of anti-HLA-class I/II IgA antibodies on graft survival. We analyzed 276 patients with and 238 without allograft failure. Eight motives of the Fcα receptor (FCAR) and Fcγ receptor were analyzed in patients with allograft failure. The distribution of anti-HLA IgA1/A2 and IgG antibodies differed significantly (p < 0.0001) between both patient groups, and IgA1 plus IgA2 antibodies were more abundant in patients with allograft failure. Allograft survival was significantly impaired if anti-HLA-class I plus II IgA was present, in the first 105 months (9 years) of follow-up (median of 43 vs. >105 months, p = 0.007). Patients with anti-HLA IgA and IgG vs. anti-HLA IgG only had a significantly shorter allograft survival within that follow-up period (88 vs. >105 months, p = 0.008). Moreover, allograft survival was shorter (p = 0.02) in carriers of GG vs. AA + AG genotypes of FCAR rs16986050. Thus, the presence of anti-HLA IgA plus IgG vs. IgG only was associated with shorter kidney allograft survival and FCAR motives may impact on graft survival.
CRIS-Team Scopus Importer:2024-12-16
Keywords: antibodies; Fcα receptor polymorphism; Fcγ receptor polymorphism; graft survival; immunoglobulin isotypes; transplantation